Urban Sustainability in Practice: Analyzing the Implementation of the Low-Carbon City Program in Makassar - Sadid Parassa, Helni; Sari, Jayanti Armida; Mujtahid, Iqbal Miftakhul; Sandi, Fadri Ari; Putro, Yusup Lintang Cahyo Andrian (Departemen Ilmu Administrasi FISIP UNHAS, 2025)
The Indonesian government, through Law Number 32 of 2009, emphasizes that a good and healthy environment is a fundamental right of every citizen. Various efforts have been made, including the development of regulations, the